Intense red emission of mixed-alkali rare-earth free germanate glass-ceramics with Mn ions; Optical Materials Express; Vol. 12, iss. 5 - Babkina A. N. Anastasiya Nikolaevna; Valiev D. T. Damir Talgatovich; Kulpina E. V. Ekaterina Vitaljevna; Pavlyuk A. S. Aleksandra Sergeevna; Zyryanova K. S. Kseniya Sergeevna; Monogarova A. A. Alina Aleksandrovna; Ignatjev A. A. Aleksey Aleksandrovich; Kuzmenko N. K. Nataljya Konstantinovna; Zhizhin E. V. Evgeny Vladimirovich; Koroleva A. V. Aleksandra Vladimirovna (2022, 2022)
Title screen